Cloud computing technology: improving small business performance using the Internet. (2nd November 2019) - Attaran, Mohsen; Woods, Jeremy
Abstract : Cloud computing technology (CCT) is a revolutionary new way of leveraging the power of the Internet to provide software and infrastructure solutions to businesses around the world. 2017 is predicted to be a major breakout year for this technology, with many organizations small and large making a shift to this platform. Employing this technology empowers communication between companies and has the potential to generate significant financial and operational benefits for small businesses. The key objective of this article is to propose a conceptual model for successful implementation of CCT in small businesses. This article also examines some of the potential benefits of CCT as applied to small businesses and explores implementation challenges that can be expected. Furthermore, this study reviews key attributes of successful CCT and illustrates some of the routes that might be taken to implement this technology in small businesses. Finally, this article examines the specific application of CCT to small businesses, highlights developing technologies and trends, investigates the deployment of CCT in different types of small businesses, and provides a case example of success.